Determination of Flow Characteristics in Technological Processes with Controlled Pressure - T. Reader; V. A. Tenenev; A. A. Chernova (Приборы и методы измерений, 2020)
Assessment of the environmental and economic performance of a safety valve requires information about the flow of the substance through the valve when it is actuated. The goal of this paper was to determine the flow rate of the discharged substance and the mass flow rate of the substance entering the safety valve when it is actuated.Proposed a mathematical model to describe the processes occurring in the valve. The model includes a system of differential equations describing the physical laws of conservation in the internal volume of the valve and differential equations, which link the value of gas flow through the valve with the pressure and the amount of movement of the shut-off disk. Used a modified method by S.K. Godunov to solve gasdynamic equations.Established that the determination of the flow and power characteristics of the valve requires the preliminary construction of a mathematical model of the safety valve operation. Based on this, proposed a method for determining the flow rate of the discharged substance and the mass rate of the substance entering the safety valve when it is actuated.Obtained the flow characteristics of the valves under review and the dynamics of movement of the shutoff disc of the valve, as well as the dependence of the pressure change on the opening time of the valve. Comparison of the calculated values with available experimental data gives good agreement of results (no more than 5.6 % for a gas flow rate, under 10 % for the movement of the valve and change the arrival of gas in time using the standard deviation function of the flow characteristics of 0.6 %), confirms the correctness of the defined mathematical model, used numerical schemes and algorithms, as well as the proposed method and recoverability of the arrival of gas in a pressure–time curve.